Effect of SOYDRA pudding (soybean and red dragon fruit) on blood pressure in patients with hypertension - Annisa Khaira Ummah; Ahmad Syauqy; Diana Nur Afifah (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Hypertension is a major risk factor for cardiovascular diseases and remains the leading cause of mortality globally. Non-pharmacological interventions using local functional foods are promising alternatives for blood pressure management. SOYDRA pudding, a novel combination of soymilk and red dragon fruit, contains bioactive compounds such as flavonoids, isoflavones, and dietary fiber, which are known to have antihypertensive properties. This study aimed to evaluate the effect of SOYDRA pudding as a dietary intervention on blood pressure in patients with grade 1 hypertension. A randomized crossover trial was conducted from September to November 2024 at the outpatient clinic of the Arosuka Hospital, West Sumatra. Thirty-two participants aged 40–60 years with grade 1 hypertension were included in this study. The intervention consisted of consuming SOYDRA puddings twice daily (2 × 150 g/day) along with nutritional education over a 30-day period. Blood pressure measurements were performed before and after the intervention. Data were analyzed using the dependent t-test and Wilcoxon test. Results, there was a statistically significant reduction in systolic blood pressure from 146,3 ± 6,2 mmHg to 132,5 ± 5,9 mmHg (p = 0,000) and in diastolic blood pressure from 92,7 ± 4,8 mmHg to 84,1 ± 4,2 mmHg (p = 0,000) after the 30-day intervention. In conclusion, the administration of the SOYDRA pudding at a dose of 2 × 150 g/day for 30 days significantly reduced both systolic and diastolic blood pressure in patients with hypertension. These findings highlight the potential of functional food-based dietary strategies in non-pharmacological hypertension management.